Determinants of Market Orientation among Smallholders Cassava Farmers in Nigeria (Global Journal of Management and Business Research, 2013)
Households need surplus output to meet both consumption requirements and market demand. To achieve this, households intuitively produce enough quantities of crops to satisfy these. Only a small proportion of the total output is taken to the more lucrative (but distant) urban markets for sale. This study aimed at analyzing the factors determining smallholder cassava farmer's market orientation. Household survey was conducted with a total of one hundred respondents. Descriptive Statistics was used in describing the socio-economic status of farmer households in the study area and Tobit model to identify factors that influenced market orientation.
Keywords: cassava; commercialization; market orienta-tion; tobit model and nigeria